In vitro dentin permeability and tubule occlusion of experimental in-office desensitizing materials - de Castro Oliveira, Laryssa [UNESP] (2023)
Objectives: This study investigates the dentin permeability (by hydraulic conductance) and tubule occlusion (by confocal and scanning electron microscopies) of in-office desensitizing materials. Materials and methods: Bovine dentin blocks were immersed in EDTA to open dentinal tubules. Placebo varnish (PLA), fluoride varnish (FLU), NaF 5% + 5% nanoparticulate sodium trimetaphosphate varnish (TMP), universal adhesive system (SBU), S-PRG filler varnish (SPRG), Biosilicate (BIOS), and amelotin (AMTN) solution were the materials tested. After application, the specimens underwent an erosive-abrasive challenge. Dentin permeability was evaluated at T0 (initial), T1 (after treatment), and T2 (after challenge). Confocal and scanning electron microscopy (SEM) were used to evaluate, respectively, length and number of dentinal tubule occlusions and opened dentinal tubules, after challenge. Permeability and SEM data were analyzed by two-way repeated measures ANOVA and Tukey’s tests. Confocal data were analyzed by one-way ANOVA, Tukey’s test, and Kruskal–Wallis and Dunn’s tests. Spearman and Pearson’s correlation tests were also used. Significance level was set at 5%. Results: At T1, the AMTN group showed the lowest permeability value, following the increasing order at T2: AMTN = SBU < BIOS = SPRG < TMP < FLU < PLA. The SBU group had the highest value of occluded dentinal tubule length. The AMTN group presented more occluded dentinal tubules compared to PLA and FLU. AMTN and SBU had the lowest values of opened dentin tubules. Results showed a negative correlation between the analyses. Conclusion: The SBU and AMTN solution were more effective in reducing dentin permeability by occluding dentin tubules. Clinical relevance: All materials reduced permeability after challenge, except fluoride varnish.